Das Verhalten einer analythischen Funktion bei grosseres Werte ihm absoluten Betrages - Streliz, S. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ш. И. Стрелиц. Поведение аналитической функции при больших значениях ее модуля Š. Strelicas. Analizinių funkcijų elgimasis, esant didelėms jų modulio reikšmėms